An experimental study on strategic preference formation in two-sided matching markets - Natsumi Shimada (Osaka University, Institute of Social and Economic Research (ISER), 2022)
We study an experiment of the students-proposing deferred acceptance mechanism (DA) in matching markets where firms are matched with students. We investigated the two different situations: (i) Students know firms' preferences and firms submit their true preference, (ii) Students know firms' preferences and firms submit a higher ranking to students who give them higher ranking. This experiment confirms that the matching results under DA in uence students' preference formation, which decreases the degree of stability. If firms do not submit their true preferences, students also do not submit their true preferences. As a result, the situation induces instability. Moreover, we find the new pattern of submitted preferences - compromise strategy. If there is an extreme option, students will tend to prefer the in-between option.
Keywords: 330; Matching; Unternehmen; Studierende; Präferenztheorie; Entscheidungstheorie